The Development of component-based information systems - De Cesare, Sergio;Lycett, Mark;Macredie, Robert D. (London, United Kingdom : Routledge, 2016)
This work provides a comprehensive overview of research and practical issues relating to component-based development information systems (CBIS). Spanning the organizational, developmental, and technical aspects of the subject, the original research included here provides fresh insights into successful CBIS technology and application. Part I covers component-based development methodologies and system architectures. Part II analyzes different aspects of managing component-based development. Part III investigates component-based development versus commercial off-the-shelf products (COTS), including the selection and trading of COTS products.
1. Development of component-based information systems: an introduction -- Part 1. Component-based development methodologies and systems architectures -- 2. An approach to component-based and service-oriented system architecture design -- 3. Toward a component-oriented methodology to build-by-integration -- 4. Principles of UML-based component modeling -- 5. Designing flexible distributed component systems -- 6. Patterns, pattern languages, and software architecture for CBDi : the lessons of the ADAPTOR experiment -- 7. Techniques and strategies for testing component-based software and product lines -- Part 2. Managing component-based development -- 8. Organizing for software product families -- 9. Business engineering of component-based systems -- Part 3. Component-based development with commercial off-the-shelf products -- 10. Selecting commercial off-the-shelf products -- 11. Trading for COTS components to fulfill architectural requirements.
Includes index.
Keywords: COMPONENT SOFTWARE